2019
DOI: 10.4253/wjge.v11.i12.573
|View full text |Cite
|
Sign up to set email alerts
|

Propofol vs traditional sedatives for sedation in endoscopy: A systematic review and meta-analysis

Abstract: BACKGROUNDPropofol is commonly used for sedation during endoscopic procedures. Data suggests its superiority to traditional sedatives used in endoscopy including benzodiazepines and opioids with more rapid onset of action and improved post-procedure recovery times for patients. However, Propofol requires administration by trained healthcare providers, has a narrow therapeutic index, lacks an antidote and increases risks of cardio-pulmonary complications.AIMTo compare, through a systematic review of the literat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 63 publications
(49 reference statements)
3
29
0
Order By: Relevance
“…Although propofol has a favorable safety and efficacy profile in comparison to other sedative regimens [ 30 , 31 ], the lack of an antidote for reversibility and the potential severe adverse events, including cardiopulmonary compromise requiring resuscitation, call for a particular caution in its use. Therefore, several anesthesiology societies and regulatory agencies recommended against the use of propofol in absence of an anesthesia specialist [ 6 , 7 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although propofol has a favorable safety and efficacy profile in comparison to other sedative regimens [ 30 , 31 ], the lack of an antidote for reversibility and the potential severe adverse events, including cardiopulmonary compromise requiring resuscitation, call for a particular caution in its use. Therefore, several anesthesiology societies and regulatory agencies recommended against the use of propofol in absence of an anesthesia specialist [ 6 , 7 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Inoue et al 15 introduced the concept of natural orifice transluminal endoscopic surgery (NOTES) 16 17 associated with submucosal dissection 18 and named this technique peroral endoscopic myotomy (POEM). Studies have shown that the short- to mid-term efficacy of POEM is greater than 90 % and that the procedure is associated with less postoperative pain 19 20 21 22 23 24 25 . However, this procedure is frequently associated with some common adverse effects, such as pneumoperitoneum and surgical emphysema 26 .…”
Section: Introductionmentioning
confidence: 99%
“…However, randomised studies have evaluated pharmacological alternatives for procedural sedation and have shown that propofol (Baxter International Inc., Deerfield, IL), compared with the use of traditional agents, has a rapid onset of action, provides predictable sedation depth and recovery times, and improves patient satisfaction rates [ 4 – 6 ]. Nonetheless, and despite its beneficial pharmacokinetic profile, propofol has a narrow therapeutic window and no antidote, highlighting the fact that it should be administered by certified health professionals using precise administration techniques to avoid critical events [ 7 ].…”
Section: Introductionmentioning
confidence: 99%